Experiences, Perspectives, and Professional Development Needs of Mental Health Nurses Caring for Women During the Perinatal Period in Acute Mental Health Settings - Sara Lamoureux; Elizabeth M. Forster; Amy E. Mitchell (Canadian Journal of Nursing Research, 2026)
Background High-quality management of mental illness for women admitted to acute mental health settings during the perinatal period is crucial due to the complexities associated with concurrent mental illness and pregnancy/childbearing. Purpose This research aimed to identify perspectives and education needs and experiences of moral distress among psychiatric nurses caring for perinatal women in acute mental health settings. Methods A convenience sample of 12 nurses from acute mental health units in public tertiary hospitals in south-east Queensland, Australia, completed a demographic survey and semi-structured interviews which were recorded, transcribed, and analysed using thematic analysis. Results Four overarching themes included: (i) Nursing Care, (ii) Work Environment, (iii) Workflow Challenges, and (iv) Moral Distress. Despite potential risks for women admitted to acute mental health units during the perinatal period, nurses provided compassionate care, demonstrated advocacy, reflected upon challenging conversations, and were cognizant of patient safety. Nurses reported limited educational preparation around perinatal mental health, and perceived deficits in continuing professional development opportunities and resources. Negative feelings associated with moral distress, including worrying and struggling, were highlighted by nurses and impacted care provision. Conclusion Nurses require support to successfully navigate providing care to this complex clinical group within equally complex health care environments, team dynamics and moral/ethical considerations.